Correlation of Serum Potassium Status and HEART Score in Acute Coronary Syndrome Patients - Verina Logito; Nida Suraya; Dewi Kartika Turbawati (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Patients with acute coronary syndrome (ACS) often experience hypokalemia which increase the risk of ventricular arrhythmia. The HEART Score can identify the prognosis of ACS. This study aimed to examine the correlation between serum potassium and HEART Score on ACS.Methods: This was a cross-sectional observational, correlative analytic study. The data were taken retrospectively using secondary data. Inclusion criteria were all ACS patients who had been examined for serum potassium parameters at the Emergency Room of Dr. Hasan Sadikin General Hospital Bandung in 2019. The HEART Score was calculated based on history (H), electrocardiogram (E), Age (A), risk factors (R), and troponin (T). Subjects were divided into low risk, intermediate risk, and high risk groups based on the HEART Score value.Results: Fifty-two ACS subjects were mostly male with a mean±SD age of 59±9 years. All subjects had moderate and high HEART scores, with 79% subjects having normokalemia. There was no correlation between HEART Score and serum potassium levels (r = -0.083, p=0.279).Conclusion: There is no relationship between serum potassium and the HEART Score that may need to determine the prognosis in ACS patients. Further study is imperative to explore serum potassium levels which might begin to decline 24 hours after the acute attack.